HUMAN–AI CO-CREATION MODELS IN CONCEPTUAL ART - Bhise, Suhas; Pradhan, Indira Priyadarsani; Keerthi, Halaharvi; Arsalwad, Gajanan P; Tolani, Kanchan; Saraswati B (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Human-ai co-creation is an important paradigm in the modern conceptual art, whereby ideas, processes and systems are prioritized over material form. This paper explores formal frameworks of human-AI collaborative creation and the way that AI is transforming the notions of authorship, intentionality, and creative agency in the context of conceptual practice. The paper is based on the conceptual art theory and co-creativity frameworks of the human-computer interaction and places AI not only as a tool, but as an active partner in the idea-based artistic generation. The study relies on a design-based research approach based on multimodal data sources such as textual prompts, sketches, generative products and interaction logs to analyse the creative decision-making process in cycles between humans and AI. Case studies Practice The practice-based case studies will illustrate how generative language models and diffusion models can be used to support conceptual exploration, allow for critical reflection, and broaden the possibilities of artistic inquiry with regard to traditional material constraints. When comparing the models of co-creation, it is possible to note that creative control, conceptual depth, and perceived authorship are different. Theoretically, the results can help change how the process of creativity is understood as a distributed phenomenon that occurs between human and AI through the interaction of the two instead of as a result of human genius.